Proses Publikasi Humas Badan Nasional Pengelola Perbatasan Pada Akun Media Sosial Instagram - Tri Baskara; Menati Fajar Rizki (CoverAge: Journal of Strategic Communication, 2019)
The National Agency for Border Management of the Republic of Indonesia as a government agency has the duty to manage the country's territorial borders. Regarding the country's borders, information is needed by Indonesian citizens to find out about what the country's borders are and what the conditions are BNPP Public Relations is the leading division to inform matters relating to the Disclosure of BNPP information. The purpose of this study was to determine the publication process by the BNPP Public Relations division on Instagram accounts and their obstacles. This research uses P.O.A.C theory and new media. This study uses a qualitative approach with a descriptive study on BNPP's Instagram account. This research was conducted at the BNPP public relations office with one Key Informant and two informants. The results of this study indicate that the public relations process of BNPP on Instagram faces obstacles. In the Planning section that is Human (HR) is lacking, then the indicators of Organizing namely Technology as the supply of workplaces and supporting technology for making publications are still lacking, then the last obstacle is Direction in which the results of this study the obstacle lies in Vertical Communication between Leaders and Staff in the process of publication. The conclusion of this research is the use of Instagram media in publications is effective enough to see the times so that it is right on target to the community.